Profile of caregivers of dependent elderly in a pandemic context: impacts on the health and work of caregivers in portugal / Perfil de cuidadores de idosos dependentes em contexto de pandemia: impactos na saúde e no trabalho de quem cuida em Portugal - Escoval, Ana (2023)
Introduction: The COVID-19 pandemic has brought new and difficult challenges for those who provide care to dependent elderly people. This study seeks to know the profile of formal and informal caregivers of elderly people with functional dependence in Portugal. Method: Online survey conducted in June-November 2021 by the National School of Public Health-NOVA of Lisbon. The questionnaire was disseminated on social networks and via email to institutions that provide care to dependent elderly people. Protocol approved by the Ethics Committee of the School. Results: Females prevailed (91.4% formal and 88% informal caregivers). Higher education level predominated in both categories. Formal caregivers were in a younger age group than family caregivers. Among formal caregivers, 55.2% claimed to receive salaries of up to €1000. More than 70% of informal caregivers claimed to provide care to a family member or relative and they had worse self-rated health. 51% of formal caregivers and 63.7% of informal caregivers reported suffering from a chronic back problem. Feelings of isolation, sadness and depression predominated among formal and informal caregivers. Conclusion: Caring work is predominantly female and the Covid 19 pandemic has had important impacts on the health of caregivers, especially mental health.